Implementation Of The Bagging-Based C4.5 Algorithm To Analyze Customer Satisfaction In Electronic Pulse - Muhamad Sulaeman; Mohamad Setiawan; M. Taufiq Irpan (Jurnal Improsci, 2025)
Background. Many users of Telkom mobile or gadgets in the world, especially in the field of mobile telecommunications technology, provide much convenience for the customer to make purchases of electronic top-up. Aims. Competition among suppliers of telecommunication service providers requires an analysis to determine the level of customer satisfaction with electronic pulses. Methods. In this study, the C4.5 and C4.5 Algorithm Based on Bagging will be used to analyze customer satisfaction, with data collected from 460 customers and 11 variables related to electronic top-up. Conclusion. This research aims to generate customer satisfaction analysis using the C4.5 and C4.5 algorithms, based on the bagging algorithm, to determine an appropriate method for analyzing customer satisfaction with electronic top-up.